I am looking for a solution to the problem:
ag_p*Gamma_p - Sa = 0 with Gamma_p = A+B*ag_p.
A, B and Sa are constants.
This can be solved by iterations starting with a certain guess value for ag_p. I tried to use the following code:
Sa = 2.7956;
A = 2.24;
B = 0.5547;
f = @(ag_p) ag_p*Gamma_p - Sa;
Gamma_p = A+B*ag_p;
z = fzero(@(ag_p) f(ag_p), 1E-3);
My code cant be run because the Gamma_p is a function of ag_p which is unknown. What would be the efficient way to tell the program to start with a guess value for ag_p ?